Análise do perfil e fatores relacionados a sobrevida de adultos jovens e idosos portadores de câncer oral - Amorim, Marília de Matos (2018)
Oral cancer represents a major public health problem with widely varying incidence, mortality, and survival rates worldwide. The disease of multifactorial etiology develops because of the interaction of multiple genetic and environmental factors. The objective of this study was to investigate the profile of patients with oral cancer and to evaluate the influence of the factors related to the survival of these individuals in a high complexity Oncology unit of Feira de Santana, Bahia, Brazil, between 2010 and 2016. It is a hospital-based, retrospective cohort study where the population was composed of individuals with histopathological diagnosis of squamous cell carcinoma. Socio-demographic, life habits, lesion data, treatment, survival time and survival status variables were obtained by reviewing clinical records. Initially, a descriptive analysis of all variables was performed. Later, the Kaplan-Meier estimator was used to compute the survival probabilities at each time, with and without stratification. The log-rank test was used for the comparisons between the several curves. In order to estimate the effects of each variable on the survival of the individuals, the Cox models were adjusted for each of them and, from the significance of the relative risks at each time, the variables that entered the multivariable model were defined. The majority of cases occurred in male individuals, aged over 45 years, chronic smokers and alcoholics. Lesions predominantly localized in the tongue were diagnosed at an advanced stage of the disease. Surgical therapy associated with radiotherapy and chemotherapy was the most recommended for the young group and radiotherapy associated with chemotherapy for the old group. Results indicated that the only predictive factors for oral cancer were tumor staging and type of treatment, pointing out the need for strategies to reduce the main risk factors for the disease and the importance of early diagnosis, to increase the patients’ survival and the improvement of their quality of life.